2003
DOI: 10.1080/01448765.2003.9755259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of White Clover Traits on Biomass and Yield in Winter Wheat- or Winter Oilseed Rape-Clover Intercrops

Abstract: The potential to usc differences in traits of white clover (Trifolium repens L.) varieties to improve mature yield of winter wheat or winter oilseed rape (Brassica napus L.) sown in white clover living mulch was studied in two field experiments conducted in Southern Sweden. The clover varieties Sonja, S 184 and AberCrest, differing in leaf size and winter hardiness, were undersown in spring barley. Three consecutive crops of winter wheat or one crop of winter rape sown at two densities followed the barley. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…However, the introduction of living mulch could induce competition between the cash crop and the living mulch (Teasdale, 1996). Most studies reported a yield reduction of the cash crop (Bergkvist, 2003;Carof et al, 2007;Picard et al, 2010;White and Schott, 1991), even if a few ones reported no yield loss (Ilnicki and Enache, 1992). Nevertheless, the yield reduction mentioned before occurred for systems where the living mulch was still growing during the main phases of yield components establishment particularly in the spring (Carof et al, 2007;Hiltbrunner et al, 2007).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the introduction of living mulch could induce competition between the cash crop and the living mulch (Teasdale, 1996). Most studies reported a yield reduction of the cash crop (Bergkvist, 2003;Carof et al, 2007;Picard et al, 2010;White and Schott, 1991), even if a few ones reported no yield loss (Ilnicki and Enache, 1992). Nevertheless, the yield reduction mentioned before occurred for systems where the living mulch was still growing during the main phases of yield components establishment particularly in the spring (Carof et al, 2007;Hiltbrunner et al, 2007).…”
Section: Introductionmentioning
confidence: 90%
“…makes it an important crop in French rotations dominated by straw cereals (AGRESTE, 2014) and justifies the design of innovative cultural practices (Valantin-Morison, 2012). Studies of brassica species based on mixed cropping are rare (Banik et al, 2000;Schröder and Köpke, 2012), especially with WOR (Bergkvist, 2003). Jamont et al (2013) demonstrated the niche complementarity of winter oilseed rape intercropped with faba bean in the early growth but this study only focused on nitrogen use and was carried out under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of legume–brassica intercropping has been investigated for various purposes in Europe, Asia, and North America, reflecting the endeavours of researchers to address problems and meet the farmers’ needs specific for these different agro-environments. In France, Sweden, and Canada, the weeds in oilseed rape are tackled by intercropping frost-sensitive legume as living mulch (Bergkvist, 2003; Thériault et al, 2009; Cadoux et al, 2015; Lorin et al, 2015). The advantage of intercropping annual legumes with cabbage and cauliflower in Turkey (Yildirim and Guvenc, 2005, 2006) and broccoli in the USA (Coolman and Hoyt, 1993) over sole crops, were demonstrated in vegetable production.…”
Section: Together In Feeding Ruminants and Soilmentioning
confidence: 99%
“…This yield reduction is likely caused by the competition for light, water and nutrients between the cover and main crop, which is, at least to a certain degree, unavoidable (Thorsted et al, 2006b). For example, low grain yields of winter wheat were typically associated with low ear densities and attributed to either poor germination or weak plants resulting from the competition exerted by the cover crops (Bergkvist, 2003a;Neumann, 2005;Hiltbrunner et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by using less competitive cover crop genotypes (Bergkvist, 2003a;Hiltbrunner et al, 2007a) or by the selective weakening of the cover crop, for example by tilling strips in which the main crop is established (Thorsted et al, 2006b). However, with both strategies the risk of less effective weed suppression is increased when compared with living mulch systems with competitive cover crops and direct seeding.…”
Section: Introductionmentioning
confidence: 99%